Fragmentation of a Turkish Low Rank Coal During Fixed-bed Evaporative Drying Process - Pusat, Saban; Akkoyunlu, Mustafa Tahir; Erdem, Hasan Huseyin (TAYLOR & FRANCIS INC, 2021)
In the present study, a new approach was utilized to investigate the fragmentation of low rank coal during the thermal drying process. Drying experiments were conducted at different drying air temperatures (70, 100, 110 and 130 degrees C), drying air velocities (0.4 and 0.7 m/s), bed heights (100, 150 and 250 mm) and particle fractions (20-50, 28-50 and 35-50 mm) for a Turkish lignite (Konya-Ilgin lignite) in a fixed-bed dryer. Konya-Ilgin lignite was used in the heating sector. Particle sizes used in these experiments were coarser than the studies in the literature due to legal constraints. The effects of drying parameters on coal fragmentation were evaluated. The fragmentation increased as the drying air temperature and the velocity increased, and it decreased as the bed height and the particle size increased. Results of this study may be used in the design of a suitable dryer for low rank coal.
Keywords: Low rank coal; lignite; fragmentation; drying; fixed-bed dryer; Energy & Fuels; Mining & Mineral Processing